Google Classroom Application in Blended Learning: Indonesian EFL Learners’ Perception - Fitriatul Masitoh; Sufirmansyah Sufirmansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2022)
Teaching English in the 21st century means that teachers are responsible for more than just teaching the subject; they are also responsible for guiding and monitoring their students as they develop and apply the 21st century skills. At this stage, both teachers and students must adapt to new technology in order to ensure the highest possible quality of teaching and learning in an offline, online, or blended classroom. The use of educational platforms, e.g. Google Classroom, enables educators to adhere to the standards for 21st-century classroom practices. The purpose of this study is to explore EFL students' perceptions on the use of Google Classroom in blended learning. We used a survey research design with a closed-ended questionnaire. The respondents were 106 EFL students from the English Language Education Department of the State Islamic Institute of Kediri. The findings indicate that the EFL learners mainly perceived positively towards Google Classroom's attributes including its usefulness, convenience of use, ease of learning, and user satisfaction when it is used in blended learning. In summary, this research adds to the body of knowledge regarding the potential of Google Classroom in blended learning.